PENGARUH LATIHAN MEMBACA DENGAN SUARA KERAS TERHADAP FREKUENSI DAN DURASI KEKAMBUHAN HALUSINASI PENDENGARAN - Linda Fitri Yanti; Sariman Pardosi; Septiyanti Septiyanti (Poltekkes Kemenkes Bengkulu, 2020)
Abstract: hallucinations Schizophrenia is a severe mental disorder that one of them is characterized by a disturbance of reality (hallucination or waham). Patients with auditory hallucinations that seem to hear voices. One of the usual ways of fighting hallucinations is to divert attention by doing activities to fill the void. This study aims to determine the effect of reading exercise aloud on the frequency and duration of recurrence of auditory hallucinations. The design used was Pre Experimental with one group pre test-post test. The sample was taken using Simple Random Sampling with 36 samples. The instrument used in this study is a questionnaire. The analysis used is non parametrick by using the Wilcoxon test. The results showed that there was a difference in frequency and duration of recurrence of auditory hallucinations (p = 0.0001) So it can be concluded There is an effect of reading practice aloud on the frequency and duration of auditory hallucinations recurrence. beliefs about the power and power of hallucinations will be weakened when patients are trained coping strategies to control hallucinations consistently. Where at the time of reading aloud the focus of attention of the patient will be diverted from the hallucinations.Keywords: Schizophrenia, hallucinations, Self Management, Activity therapy.